Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/slct.202204256
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Benzo[d] thiazolyl‐Sulfonyl‐Benzo[4,5]isothiazolo [2,3‐c][1,2,3] triazole Derivatives as EGFR Targeting Anticancer Agents

Abstract: A one‐step procedure for the synthesis of new fused Benzo[d]thiazolo‐1,2,3‐triazoles (3 a–3 h and 4 a–4 h) in good yields using sulfonylazides (2) and iodoalkyne (1) through from the 5‐iodo 1,2,3‐triazole generated in situ was developed. Among all, compounds 5‐chloro‐3‐(((1,1‐dioxidobenzo[d]thiazol‐2‐yl)sulfonyl)methyl)benzo[4,5]isothiazolo[2,3‐c] [1,2,3]triazole 8,8‐dioxide (3 e), 3‐(((1,1‐dioxidobenzo[d]thiazol‐2‐yl)sulfonyl)methyl)‐5‐fluorobenzo[4,5]isothiazolo [2,3‐c][1,2,3]triazole 8,8‐dioxide (3 f), 5‐br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Similarly, carboxyamidotriazole (CAI), a clinical trial phase II anticancer agent [22] . and also our research group previously reported sulfonyl‐1,2,3‐triazoles (A and B) as potent EGFR‐targeting anticancer agents, as shown in Figure 1 [13,15] …”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Similarly, carboxyamidotriazole (CAI), a clinical trial phase II anticancer agent [22] . and also our research group previously reported sulfonyl‐1,2,3‐triazoles (A and B) as potent EGFR‐targeting anticancer agents, as shown in Figure 1 [13,15] …”
Section: Introductionmentioning
confidence: 60%
“…[22] and also our research group previously reported sulfonyl-1,2,3triazoles (A and B) as potent EGFR-targeting anticancer agents, as shown in Figure 1. [13,15] To begin with, Meldal and Sharpless revealed the Cu and Ru-catalysed cycloaddition routes to create regioselective 1,4and 1,5-disubstituted 1,2,3-triazoles, [23,24] which were confined to terminal alkynes. However, the effective building of the ring structure of 1,2,3-triazole without the use of transition metal catalysts and terminal alkynes is also an important issue in pharmaceutical synthesis and organic molecule bioconjugation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzo [4,5]isothiazolo [2,3- c] [1,2,3] triazole-benzo[d]thiazole hybrid 13 (IC 50 : 4.47 µM, MTT assay) was comparable to erlotinib (IC 50 : 4.15 µM) against MCF-7 breast cancer cells and merited further investigations. [33] 1,2,3-Triazole-thiazolidine-2,4-dione hybrids 14 (IC 50 : 0.33-1.64 µM, MTT assay) exhibited potent antiproliferative activity against MCF-7 breast cancer cells, and hybrids 14a-c (IC 50 :330-560 nM) were not inferior to CA-4 (IC 50 : 180 nM). [34] Hybrids 15 (IC 50 : 17.61-26.04 µM, MTT assay) possessed moderate activity against MCF-7 breast cancer cells, and the SAR indicated that substituent on the para-position of phenyl ring reduced the activity.…”
Section: 23-triazole-azole Hybridsmentioning
confidence: 99%